(untitled) (Palestine Issues on Indonesian Society, 2025)
This paper explores the rise of Boycott, Divestment, Sanctions (BDS) campaigns in Indonesia and their relationship to consumer nationalism in the context of Palestinian solidarity. Focusing on the intersection of social activism, consumer behavior, and political identity, the study examines how Indonesian activists and civil society groups have used boycott campaigns as a tool to protest Israeli policies and support Palestinian rights. It investigates how these campaigns have mobilized local consumers to boycott Israeli goods, companies with ties to Israel, and global brands perceived as complicit in the occupation of Palestinian territories. The paper also considers the role of social media in amplifying the BDS movement, examining how Indonesian activists utilize digital platforms to spread information and rally public support. Furthermore, the study addresses the challenges and controversies surrounding BDS in Indonesia, considering the ethical and political implications of consumer nationalism and its potential to influence international relations and corporate practices. The paper concludes by evaluating the effectiveness of boycott campaigns as a form of solidarity activism within the Indonesian context.